BUDAYA SCROLLING DI PLATFORM TIKTOK TERHADAP PERILAKU HABLUMINALLAH DAN HABLUMINANNAS MAHASISWA PAI - Tamim, Ahmad Roihan; Noval Vahmi Varhan (Guruku: Jurnal Pendidikan Profesi Guru, 2024)
TikTok is the fastest growing social media platform in the world, ahead of Facebook and Instagram. As of April 2024, Indonesia ranks first in active TikTok users with 127.5 million users. Based on a DataIndonesia.id survey, TikTok users in Indonesia increased by 19.1% from November to January 2024, marking a phenomenon of TikTok scrolling culture. This study examines for impact of TikTok scrolling culture on the religious behavior of Islamic Religious Education (PAI) students at UIN Raden Mas Said Surakarta. The research uses a qualitative approach and make interview method. The results show that students started using TikTok in 2020 during pandemic. students spend 1-6 hours per day on TikTok, they still carry out religious activities (Habluminallah) such as prayer, fasting, zakat, pilgrgambar, and reading the Koran. TikTok also has content that motivates students to carry out worship. The influence of TikTok on students' social relationships (Habluminannas) shows that most of them still obey their parents and teachers, behave politely, and use good speech. However, excessive use of TikTok can affect the consistency and quality of worship. This study reveals that good time management allows the use of TikTok without interfering with religious activities and social relationships.